MENINGKATKAN LITERASI KEUANGAN UMKM MELALUI SOSIALISASI DAN PELATIHAN LAMIKRO DI KECAMATAN DAYUN - Mariaty Ibrahim; Ruzikna Ruzikna; Mashur Fadli; Jeneva Augustin (Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
Lamikro application not only provides practical features that are easily accessible but also provides free access for every business owner. However, many people are not familiar with and know this application so it is important to provide socialization so that not only knowing, MSMEs can use it for business purposes. The purpose of this service is to socialize MSME actors about the Lamikro application to increase knowledge and encourage the use of these applications for financial bookkeeping. Participants in this service amounted to 20 people who were representatives of MSMEs in Dayun District. The service method uses a PAR approach, which is carried out by delivering material, discussion and evaluation. Lamikro socialization activities can be carried out well. Participants took part in the activity seriously and enthusiastically. From the evaluation of training on the use of the Lamikro application, it shows that most participants, namely 90% of participants understand the material very well, while the other 10% understand it well. This result reflects a high level of success in socializing the application to micro business actors. In addition, the skills evaluation also showed that participants not only understood the theory of financial management, but were also able to practice it well. Recommendations from this service activity need intensive assistance from related agencies in encouraging financial digitalization for MSMEs, especially business bookkeeping. This effort is made so that they can run their business more effectively and efficiently and have ideal competitiveness in the era of society 5.0.